(untitled) (Journal of NELTA, 2024)
The education system in Bangladesh predominantly follows a long tradition of classroom-based face-to-face teaching. However, with the sudden outbreak of Covid 19, teaching across the country had to shift from offline classes to online platforms. This sudden shift put English teachers under strain and posed challenges regarding teaching-learning practices and classroom management. Using a mixed-method approach, this study explores the perceptions, experiences, and needs of tertiary level English teachers in Bangladesh regarding online teaching. Though marked by mixed perceptions about online pedagogy, the study demonstrates English teachers’ propensity to replicate face-to-face classroom teaching techniques in online classes. The findings also highlight the need for teacher training on using various learning management systems (LMS). Additionally, teachers require guidance on how to engage students, provide feedback, and conduct assessments in online classes. The findings of the study have implications for teachers in conducting online classes, teacher trainers in designing training modules, and policymakers in devising appropriate policy for online teaching at the tertiary level education in Bangladesh.